Connectivity Indonesia’s Maritime Global Axis Policy - Christine Sri Marnani; Freddy Johanes Rumambi; Haposan Simatupang (The Republic of Indonesia Defense University, 2016)
This research aims to analyze the concept of connectivity forms Axis World Maritime Indonesia with One Belt One Road (OBOR) and see the implementation of cooperation with China and its benefits for Indonesia. This study uses a qualitative method eksplanatif. The data collection technique using observation, interviews with sources and literature. Research found that Indonesia has a great opportunity to work together in realizing the PMD and the Maritime Silk Road of the 21st century to emerge as a global player. OBOR concept including the construction of the Maritime Silk Road, not merely based on economic interests but part of a political strategy of China's exit from US domination and its allies. In addition to building political influence in the countries included in the construction of the Maritime Silk Route.